Global government in the works of H. G. Wells, A. Huxley and G. Orwell - Benedikt, Jan (Univerzita Pardubice, 2019)
This master thesis deals with the comparison of approaches to the concept of Global government in works of H. G. Wells, A. Huxley, and G. Orwell. The concept of the Global government is exactly defined, acquired data are then applied to the chosen works. Then, the chosen works are analysed and the approach of each author is precisely defined. Results of the analyses are then evaluated and used in a comparative analysis in the context of the other authors' works.
Světová vláda v díle H. G. Wellse, A. Huxleye a G. Orwella
Keywords: global government; socialism; Huxley, Aldous; Wells, Herbert George; Orwell, George; světová vláda; socialismus; Huxley, Aldous; Wells, Herbert George; Orwell, George